The Effect of High Knowledge on Diabetes Type 2 and Strong Belief in Medicine with Non-Adherence of Anti Diabetic Medication: A Meta-Analysis - Iswahyuni, Sri; Herbasuki, Herbasuki; Sunaryanti, Sri Sayekti Heni; Atmojo, Joko Tri; Rejo, Rejo; Widiyanto, Aris (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: By 2045, the number of people with diabetes mellitus (DM) was expected to increase from 424.9 million in 2017. Healthcare professionals have had a difficult time managing diabetes because of nonadherence to therapy. Additionally, the efforts made to clarify and enhance patient adherence to their medication are not always successful. This study investigated the factors such as high knowledge on diabetes type 2 and strong belief in medicine that lead to medication non-adherence in adults.Subjects and Method: This article was a systematic review and meta-analysis study conducted by searching for articles from online databases such as EBSCO, ProQuest, and PubMed. Populations: adults with diabetes mellitus; Intervention: a strong belief in anti-diabetic medication and high knowledge of diabetes mellitus; Comparison: a weak belief or none in anti-diabetic medication and little knowledge of diabetes mellitus; Outcome: non-adherence of anti-diabetic medication. The independen variables is strong belief and high knowledge, the dependen variable is non-adherence to anti-diabetic medication. The inclusion criteria for this study were full articles using a cross-sectional study, with the publication year until 2022. We conduct the analysis using RevMan 5.3 software.Results: A total of 6 articles reviewed in the meta-analysis (consisted 4 articles in each variables), from countries: Ethiopia, Australia, Uganda, Iran, Palestine and China, showed that respondents with strong belief in anti-diabetic medicines (aOR= 0.66; 95% CI= 0.48 to 0.90; p= 0.008) and high knowledge of diabetes mellitus (aOR= 0.85; 95% CI= 0.79 to 0.93; p= 0.0005) had lower level of non-adherence to anti-diabetic medication.Conclusion: A strong belief in anti-diabetic medicines and high knowledge of diabetes mellitus can lower non-adherence to anti-diabetic medication.Keywords: diabetes mellitus type 2, medication adherence, predictorsCorrespondence: Sri Iswahyuni. Study Program of Nursing, School of Health Sciences Mamba’ul ‘Ulum Surakarta. Jl. Ring Road 03, Surakarta 57127, Jawa Tengah. Email: iswahyunisri@yahoo.co.id. Mobile: +62 815-6720-715.Indonesian Journal of Medicine (2022), 07(02): 150-160https://doi.org/10.26911/theijmed.2022.07.02.04